Focus : elevating the essentials to radically improve student learning - Schmoker, Michael J. (ASCD, 2011)
The introduction states: "The only reason our schools haven't made astonishing progress in the last 30 years of "reform" is quite simple: very few schools ever implemented 'what is essential'--the most powerful, simple actions and structures that would dramatically increase the proportion of students prepared for college or careers. What is 'essential' for schools? Three simple things: reasonably coherent curriculum (what we teach); sound lessons (how we teach); and far more purposeful reading and writing in every discipline, or authentic literacy (integral to both what and how we teach).